INNOVATIVE DELIBERATIVE DEMOCRATIC APPROACHES IN TRANSITION: THE CASE OF UKRAINE - DMYTRO VOLODIN; MAKSIM MOSKALOV (Challenges of the Knowledge Society)
The article dedicates with the problem of deliberation democracy mechanism formation and development, especially for post-communist countries. Moreover, some opportunities for deliberation development according to intellectual capital of public administration are observing.